The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1039/c9ew00426b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced adsorption of perfluoro alkyl substances for in situ remediation

Abstract: Numerous groundwater sites around the globe have been contaminated by aqueous film forming foam (AFFF) as a result of firefighting, fire training activities and the storage and accidental spillage of AFFF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Testing for the ex situ treatment of PFAS-impacted water using activated carbon and ion-exchange resin (IER) have been studied extensively, However, only limited laboratory testing of reagents for the in situ treatment of PFAS have been conducted. Aly et al (2019) demonstrated that cationic polymers mixed with soil can be effective in attenuating various PFAS in column studies, while Wang and Shih (2011) and Barajas (2019) showed that alumina and biochar can act as adsorbents for PFAS, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Testing for the ex situ treatment of PFAS-impacted water using activated carbon and ion-exchange resin (IER) have been studied extensively, However, only limited laboratory testing of reagents for the in situ treatment of PFAS have been conducted. Aly et al (2019) demonstrated that cationic polymers mixed with soil can be effective in attenuating various PFAS in column studies, while Wang and Shih (2011) and Barajas (2019) showed that alumina and biochar can act as adsorbents for PFAS, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The mobilizing amendments help to desorb PFAS compounds that are bound to soil minerals or organic matter, and hence increase their bioavailability and mobility (Milinovic et al, 2015(Milinovic et al, , 2016Pan et al, 2009;Tang et al, 2017). In contrast, the immobilizing amendments adsorb or fix the PFAS compounds in soils reducing their bioavailability and mobility (Aly et al, 2019;Das et al, 2013;Hale et al, 2017). This review discusses all the above strategies by first presenting an overview of various soil PFAS sources, PFAS interactions with soil components and bioavailability, soil PFAS remediation through manipulating the bioavailability using conventional and advanced soil amendments along with some exemplary case studies, and highlighting their respective techno-economic advantages and disadvantages.…”
Section: Supplementary (Si) Figuresmentioning
confidence: 99%
“…Some liquid-based amendments were also used to facilitate PFAS immobilisation in contaminated solid media. For example,Aly et al (2019) observed a six-fold increase of PFAS retention in contaminated soils by applying a commercially available coagulant. Similarly,Pan et al (2009) calculated the thermodynamic index of irreversibility (TII) for PFOS to sediments in the presence of a cationic surfactant, cetyltrimethylammonium bromide (CTAB), to quantify the degree of sorption irreversibility caused by CTAB, with a value of 0 representing a highly reversible system and 1 representing irreversible sorption.…”
mentioning
confidence: 99%
“…The most applied technologies for the treatment of PFAS in water treated above ground are systems utilize activated carbon and ion‐exchange resin. Limited laboratory and field studies have been conducted looking at the possibility of using in situ methods to address PFAS‐impacted groundwater (Aly et al, 2019; Barajas, 2019; Bruton & Sedlak, 2017; Carey & McGregor, 2019; Dombrowski et al, 2018; Eberle et al, 2017; Liu et al, 2020; McGregor, 2018; McGregor, 2020; Park et al, 2016). The use of in situ methods for the treatment of PFAS offers several advantages over extraction technologies including lower costs and flexibility.…”
Section: Introductionmentioning
confidence: 99%